Management of Dental and Orthodontic Practice in the COVID-19 Scenario - Syed wajahat Mohammad Razavi; Chanjyot Singh Walia (Tehran University of Medical Sciences, 2022)
The coronavirus disease-2019 (COVID-19) pandemic due to the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has casted a deep impact on every aspect of the human life all over the world. The healthcare professionals dealing with the patients have been at the greatest risk of exposure. Dental practitioners fall among the highest risk practitioners because of their field of operation being around the oropharyngeal region of patients, as well as due to the risk of generation of aerosols during various dental procedures. There is a continuous urgent need of modifying the dental practice in accordance with the guidelines issued by the health authorities time to time. Meticulously planned approaches, and adequate precautions and modifications need to be introduced into dental practice. The field of orthodontics also demands a high level of practice modification in order to ensure proper infection control for patients, practitioners, and dental staff.